The Implementation of Simple Additive Weighting (SAW) Method to Selection of Plastic Raw Materials - Andre Hasudungan Lubis; Zulfikar Sembiring; Indah Sari Gaurifa (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Plastic is a polymer material widely used as a food and beverage packaging material due to the lightness and easy to use. The selection of quality plastic raw materials from industries engaged in plastic production are greatly affects the products produced. However, there are some mistakes occurred due to the selection process is carried out subjectively without any consideration, resulting in material losses for the company. The difficulty in determining superior plastic raw materials is one of them. The study attempts to select the best plastic raw materials using the Simple Additive Weighting (SAW) method. The research use five criteria for types of raw materials, namely: price, quality, production speed, plastic waste, location. Then, the plastic seeds brands used in this study are: Poly-max, El-pro, Titan, Polytan, and Trilene. The result of the study shows various result and present which seeds is the best to be used in the company.